Structural Convergence under Reversible and Irreversible Monetary Unification. - Roel M.W.J. Beetsma; Henrik Jensen (University of Copenhagen, Economic Policy Research Unit (EPRU), 1999)
We explore endogenous monetary unification in the context of a model in which a country with serious structural distortions (and, hence, high inflation) is admitted into a monetary union once its economic structure has converged sufficiently towards that of the existing participants. If unification is reversible, so that the new entrant can always be forced to leave the union again later, convergence stops for a while after the high inflation country has joined. With irreversible unification, temporary divergence occurs, and unification is most likely to be delayed.
Keywords: 330